Plan de Seguridad y Salud Ocupacional para realizar acciones preventivas en los trabajadores del asadero “El Pollo Dorado” de la ciudad de Loja. - l Vargas flores, Sandra Cecibel (2024)
The research entitled "PLAN OF OCCUPATIONAL SAFETY AND HEALTH TO CARRY OUT PREVENTIVE ACTIONS IN THE WORKERS OF THE ASADERO EL POLLO DORADO IN THE CITY OF LOJA", has the general objective of diagnosing occupational safety and health in the Asadero El Pollo Dorado in the city of Loja and proposing an occupational safety and health plan. Its specific objectives include analyzing the current situation regarding occupational safety and health, identifying the occupational risk factors and working conditions that give rise to occupational diseases in workers and making a proposal for an occupational safety and health plan to carry out preventive actions in the workers of the Asadero El Dorado in the city of Loja. For the elaboration of this research we used descriptive and non-experimental methods, direct observation techniques, surveys to 5 workers, an interview with the manager of the asadero and an observation guide, which serves to verify the current situation of the asadero. The results of the study revealed significant risks associated with the work activity, as well as a lack of knowledge on the part of the employees and the manager on occupational health and safety issues. The absence of emergency drills and the lack of training in areas such as fire, first aid, and fire extinguisher handling were noted. In addition, there was no safety plan at the steakhouse. These findings were fundamental for diagnosing the current situation of the establishment and developing the proposed plan.